Ginsenoside Rb1 Produces Antidepressant-Like Effects in a Chronic Social Defeat Stress Model of Depression Through the BDNF–Trkb Signaling Pathway - Jiang, Ning; Huang, Hong; Zhang, Yiwen; Lv, Jingwei; Wang, Qiong; He, Qinghu; Liu, Xinmin (Frontiers in Pharmacology, 2021)
Ginsenoside Rb1 (Rb1), an important bioactive ingredient of Panax ginseng, has potent neuroprotective effects with relatively low toxicity. The main objective of the study is to explore the antidepressant-like activity of Rb1 in the depression mouse model established by inducing chronic social defeat stress (CSDS). According to the obtained results, the daily oral administration of Rb1 (35 and 70 mg per kg of total body weight) for 28 days alleviated the social avoidance behavior, anhedonia, and behavioral despair via CSDS exposure, as demonstrated by the significantly elevation in the time in the zone in SIT and consumption of sucrose solution in SPT, and decrease of immobility time in FST. Moreover, Rb1 treatment was able to reverse the CSDS-activated reduction in the hippocampal BDNF level in parallel to the elevation in adult hippocampal neurogenesis (HN). In addition, the down-regulated levels of ERK, AKT, and CREB phosphorylation in the hippocampus was observed in the CDSD-exposed mice. Further, the Rb1 treatment ameliorated the mentioned changes. Importantly, the antidepressant effects of Rb1were completely blocked in mice by using K252a (the tyrosine kinase B inhibitor). In conclusion, the obtained results revealed antidepressant effects for that Rb1 CSDS model facilitated by enhancing the BDNF signaling cascade and up-regulation of HN. Thus, it can be inferred from these findings that Rb1 can be a potent and effective candidate agent for the prevention as well as treatment of depression.